2019
DOI: 10.3390/nano9070928
|View full text |Cite
|
Sign up to set email alerts
|

Chitlac-Coated Thermosets Enhance Osteogenesis and Angiogenesis in a Co-culture of Dental Pulp Stem Cells and Endothelial Cells

Abstract: Dental pulp stem cells (DPSCs) represent a population of stem cells which could be useful in oral and maxillofacial reconstruction. They are part of the periendothelial niche, where their crosstalk with endothelial cells is crucial in the cellular response to biomaterials used for dental restorations. DPSCs and the endothelial cell line EA.hy926 were co-cultured in the presence of Chitlac-coated thermosets in culture conditions inducing, in turn, osteogenic or angiogenic differentiation. Cell proliferation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The use of NAC modulatory capabilities to alleviate the inflammatory and oxidative state of challenged pulp is part of a growing effort to facilitate the growth, healing, and function of the tissue [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of NAC modulatory capabilities to alleviate the inflammatory and oxidative state of challenged pulp is part of a growing effort to facilitate the growth, healing, and function of the tissue [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor beta (TGF-β), interleukin-6 (IL-6), interleukin-10 (IL-10), hepatocyte growth factor (HGF), prostaglandin E2 (PGE2), and human leukocyte antigen G (HLA-G) are secreted by DPSCs as anti-inflammatory cytokines. We previously reported that the inducible cyclooxygenase (COX2) is involved in the modulation of inflammation events in the presence of collagen membranes for periodontal bone and peri-implant defect treatments [23], and that PGE2 production can be involved in many differentiation processes, including osteogenic and angiogenic differentiation in the presence of biomaterials [19,24]. However, the anti-inflammatory effects of DPSCs during biomaterial integration after implantation are still poorly understood, and there is growing interest in studying the immunomodulatory effectiveness of DPSCs [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability and metabolic activity were measured using an MTT (3(4,5-dimethylthiazol-2yl)-2,5-diphenyl tetrazolium bromide) growth assay (Sigma-Aldrich, Saint Louis, MO, USA), as previously described [ 52 ]. The cultured medium was removed and washed once with 1X PBS.…”
Section: Methodsmentioning
confidence: 99%